KNOWLEDGE AND MALPRACTICES IN PEDIATRICS DIARRHEA MANAGEMENT BY IRAQI MOTHERS - Mohammed, Samer Imad; Sabry, Aya Thaer; Sabry, Dania Thaer; Mohammed, Borooj Hassan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: In developing countries like Iraq, diarrhea was responsible for 70% of deaths among pediatrics. This study was designed to determine Iraqi mothers’ knowledge and malpractices associated with diarrhea management in pediatrics. Methods: A cross-sectional pilot study was done on a convenient sample of mothers in Baghdad â€“ Iraq. Data collection was done using a validated questionnaire specifically designed for this study. Result: Most participants preferred to consult physicians or pharmacists about pediatrics diarrhea management. Breastfeeding was stopped by 19% of participants, whereas 35% of mothers who depend on formulated milk discontinued it. Only 30% of participants use oral rehydration solution therapy always as a part of treatment. Although 54% of participated mothers certainly not used antibiotics for the diarrhea management before doctor consultation, however 52.5% of these mothers used antimotility suspensions without any consultation. 17% of participants used some herbal preparations in addition to 11% used some forms of traditional harmful preparations (Al-Sagwa) to manage diarrhea. Conclusions: This study indicates a good level of knowledge about diarrhea management for most participants, although there are some wrong concepts which followed by a small percentage of mothers, especially the most dangerous malpractices of using Al-Sagwa.